Nausea and vomiting as major presenting symptoms of thyrotoxicosis after bilateral adrenalectomy for Cushing’s disease - Kogan, Yana; Elias, Nizar; Sheikh-Ahmad, Mohammad; Odeh, Majed (International Journal of Research in Medical Sciences, 2018)
Thyrotoxicosis has a variety of presentations which depend on its severity and duration, as well as the age of the patient. In elderly patients, thyrotoxicosis may present with a variety of nonspecific symptoms. Nausea and vomiting as major presenting symptoms of thyrotoxicosis have rarely been reported. Thyrotoxicosis after adrenalectomy in patients with Cushing’s syndrome and normal thyroid function, or with autoimmune thyroid dysfunction has rarely been reported previously. We describe a very rare case of an elderly patient with hypothyroidism due to Hashimoto’s thyroiditis who presented with persistent nausea and vomiting as major presenting symptoms of thyrotoxicosis, which developed after bilateral adrenalectomy for Cushing’s disease. Similar case has not been reported previously. In reporting this patient we aim at drawing attention to these forgotten symptoms of thyrotoxicosis, nausea and vomiting, and to emphasize that, at times, these symptoms may be the only presenting features of thyrotoxicosis, leading to considerable difficulty in diagnosis. Furthermore, cessation of glucocorticoid excess may sometimes be accompanied with thyrotoxicosis.